Reduced orienting to audiovisual synchrony in infancy predicts autism diagnosis at 3 years of age - Falck-Ytter, T.; Nyström, P.; Gredebäck, G.; Gliga, T.; Bölte, Sven (Wiley-Blackwell Publishing Ltd, 2018)
Background: Effective multisensory processing develops in infancy and is thought to be important for the perception of unified and multimodal objects and events. Previous research suggests impaired multisensory processing in autism, but its role in the early development of the disorder is yet uncertain. Here, using a prospective longitudinal design, we tested whether reduced visual attention to audiovisual synchrony is an infant marker of later-emerging autism diagnosis. Methods: We studied 10-month-old siblings of children with autism using an eye tracking task previously used in studies of preschoolers. The task assessed the effect of manipulations of audiovisual synchrony on viewing patterns while the infants were observing point light displays of biological motion. We analyzed the gaze data recorded in infancy according to diagnostic status at 3 years of age (DSM-5). Results: Ten-month-old infants who later received an autism diagnosis did not orient to audiovisual synchrony expressed within biological motion. In contrast, both infants at low-risk and high-risk siblings without autism at follow-up had a strong preference for this type of information. No group differences were observed in terms of orienting to upright biological motion. Conclusions: This study suggests that reduced orienting to audiovisual synchrony within biological motion is an early sign of autism. The findings support the view that poor multisensory processing could be an important antecedent marker of this neurodevelopmental condition.